Arguments among siblings: Format tying as a resource in conflict talk and conflict resolution. (August 2022) - Rodgers, Erin; Fasulo, Alessandra
Abstract: Sibling interaction is a key socializing arena for language practices due to the variety of age and position of the siblings; the ever-looming possibility of conflict also equip children with abilities for conflict management and resolution. Using Conversation Analysis, this study examines data from videorecordings of a family including two parents and four children under the age of twelve during mealtimes and play. The analysis focuses on format tying, i.e. a way to produce new turns-at-talk by incorporating parts of a previous turn, within conflict talk among the siblings. We illustrate two functions of format tying: the first is in lending structure to argumentative moves, where format tying reveals affordances for escalating conflict. The second is the transformation of an initial conflict into verbal play, with the repetition triggering language reflexivity. Finally, we discuss format tying as a readily available resource for engagement within the siblings group, and its contribution to family politics.